Pengaruh Integritas dan Disiplin Kerja terhadap Kualitas Pelayanan di Kecamatan Jatinangor - Gilang , Riki; Zuarko Adji, Wilma (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The study aims to determine how influential integrity and work discipline are on the quality of service in Jatinangor sub-district. The author researched using quantitative methods. The population of this study is people in the Jatinangor area. The analysis techniques used are validity tests, reliability tests, t tests. Sample tests chosen by researchers are sampling as many as 40 respondents. The results of this study stated that there was a significant influence of integrity (X1) and work discipline (X2) on service quality (Y) in Jatinangor sub-district by 74.9%, while there were other factors that influenced 25.1%.